The Effect of Potato Almond Orange Cookies on their Weight, BMI, Hemoglobin, and Lymphocyte Status of Undernourished Older People during COVID-19 Pandemic - Fatmah (Current Nutrition & Food Science, 2021)
Background: Older people vulnerability to COVID-19 is related to the presence of comorbidities, diseases, and low immunity. Undernutrition conditions make them prone to anemia (low hemoglobin/Hb), and low lymphocyte level brings a higher risk for COVID-19 infection. Objective: To assess the effect of potato almond orange cookies on weight, Hb, and lymphocyte levels of undernourished older people amidst the COVID-19 pandemic. Methods: This 3-week randomized controlled trial involved 48 subjects > 60 years, divided randomly into treatment group (potato almond orange cookies) and control groups (potato almond cookies). Lymphocyte and Hb were collected before and after the study. Both groups received nutrition education. The analysis was performed using an independent t-test and paired t-test. Results: Weight gained in the treatment group (0.7 kg) was significantly different from the control group (p=0.002), with a 0.3 point change observed in the BMI of the treatment group. Changes were also seen in vitamin C intake in treatment group (+10.3 mg, p = 0.03) and vitamin E intake in both groups (+4.6 mcg, p = 0.001 and +2.9 mcg, p = 0.001, respectively), but not for inter-group. Weight, Hb, and lymphocyte level increased in both groups, with the highest weight increased in the treatment group while the highest Hb increased in the control group. The lymphocyte increased 1 point in both groups. Weight, Hb, and lymphocyte level differences were insignificant between the two groups. Conclusion: Potato almond orange consumption tends to increase weight, Hb, and lymphocyte level in undernourished older people during the COVID-19 pandemic.
Keywords: weight